VNN3, a potential novel biomarker for benzene toxicity, is involved in 1, 4-benzoquinone induced cell proliferation. (February 2018) - Sun, Pengling; Guo, Xiaoli; Chen, Yujiao; Zhang, Wei; Duan, Huawei; Gao, Ai
Abstract: Benzene is widely employed in the field of production, and its toxicity on biological systems has received increasing attention. Cell proliferation is a major life characteristic of living organisms. KLF15 and NOTCH1 are mature and classical genes in cell proliferation studies, particularly in the area of tumor investigation. The aim of this study was to investigate the effect and mechanism of VNN3 on cell proliferation induced by 1, 4-benzoquinone (1, 4-BQ), an important metabolite of benzene, and obtain a sensitive biomarker for the hazard screening and health care of benzene exposure. Normally growing AHH-1 cells were cultured in vitro and were incubated with different concentrations of 1, 4-BQ (0, 10, 20, and 40 μM) for 24 h. A CCK-8 assay was used to assess the cell viability, whereas EdU was used to detect the cell proliferation of AHH-1 cells. The expression of VNN3, KLF15 and NOTCH1 was detected by real-time PCR. Moreover, a lentiviral model was constructed in AHH-1 cells to interfere with VNN3 expression. The results showed that 1, 4-BQ clearly increased the expression of VNN3. Moreover, 1, 4-BQ dose-dependently inhibited cell proliferation and caused increased KLF15 expression; in contrast, the NOTCH1 expression decreased in AHH-1 cells. Furthermore, following interference with the VNN3 expression, the cell proliferation inhibition and the expression of KLF15 and NOTCH1 were rescued. To further investigate the action of VNN3 in benzene hematotoxicity, we assessed it in benzene-exposed workers. The results showed that there was a remarkable correlation between the VNN3 expression and hemogram, which included RBC, NEUT and HGB. In addition, analysis of the KLF15 and NOTCH1 expression showed that the VNN3 expression was related to cell proliferation, which was consistent with the in vitro results. In conclusion, VNN3 influences cell proliferation induced by 1, 4-BQ by regulating the expression of KLF15 and NOTCH1. VNN3 may represent a potential biomarker of benzene toxicity. Highlights: 1, 4-BQ increases VNN3 expression and dose-dependently inhibits cell proliferation. VNN3 influences cell proliferation induced by 1, 4-BQ through the regulation of KLF15 and NOTCH1 expression. VNN3 may be used as a potential biomarker of benzene toxicity. Abstract : VNN3 influences cell proliferation induced by 1, 4-BQ through the regulation of KLF15 and NOTCH1 expression, and it may be a potential biomarker of benzene toxicity.